Investigation the Biological Activities of Chenopdium foliosum Methanol Extract - Vazgeçen, Özge; Taskin, Irmak Icen; Sever, Meryem Rüveyda; Sancar, Pelin Yılmaz (My University, 2024)
The genus Chenopodium is distributed almost all over the world, including Turkey. The species belonging to this genus are used in the traditional medicine of different countries in the treatment of various diseases. Different species of the genus Chenopodium show anticancer, antifungal, and antibacterial effects. There is a sig- nificant gap in the literature regarding Chenopodium foliosum (C. foliosum). In this study, the biological activities of the methanol extract of C. foliosum were investi- gated. The anticancer activity was evaluated using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay against HCT116 and A549 cell lines. The antibacterial and antifungal activity were examined using the minimum inhibitory concentration (MIC) assay. Methanol extract of C. fo- liosum reduced cell viability of HCT116 and A549 cell lines to 73.4 ± 3.3 % and 78.7 ± 2.3 % respectively. C. foliosum also decreased the viability of the Candida albicans (C. albicans) to 91.2 %. Our research suggests that the methanol extract of C. folio- sum slightly reduces the viability of HCT116 and A549 cell lines.
Keywords: Chenopodium; anti-cancer; anti-fungal; anti-bacterial